Relationship of serum total cholesterol and triglyceride with risk of mortality in maintenance hemodialysis patients: a multicenter prospective cohort study - Yan Huang; Qiuxia Zhong; Junzhi Chen; Xianhui Qin; Yaya Yang; Yanhuan He; Zizhen Lin; Yumin Li; Shenglin Yang; Yongxin Lu; Yanhong Zhao; Yaozhong Kong; et al. (Renal Failure)
Objective The relationship between serum total cholesterol (TC) and triglyceride (TG) levels and mortality in maintenance hemodialysis (MHD) patients remains inconsistent. We aimed to explore the individual and combined association of TC and TG levels with the risk of mortality in Chinese MHD patients.Methods 1036 MHD patients were enrolled in this multicenter, prospective cohort study. The serum levels of total cholesterol and triglycerides were measured at baseline. The primary outcome was all-cause mortality and secondary outcome was cardiovascular disease (CVD) mortality.Results During a median follow-up duration of 4.4 years (IQR= 2.0–7.9 years), 549 (53.0%) patients died, and 297 (28.7%) deaths were attributed to CVD. Compared with patients with TC levels in the first three quartiles (<182.5 mg/dL), a significantly higher risk of all-cause mortality was found in participants with TC in the fourth quartile (hazard ratio [HR], 1.43; 95% confidence interval [CI], 1.17–1.76). However, a significantly lower risk of all-cause mortality was observed in participants with TG in the fourth quartile (≥193.9 mg/dL) (HR, 0.78; 95%CI: 0.63–0.98), compared with participants with TG in the first three quartiles. Similar trends were observed in CVD mortality. When analyzed jointly, patients with lower TC (<182.5 mg/dL) and higher TG (≥193.9 mg/dL) levels had the lowest risk of all-cause mortality and CVD mortality.Conclusions: In MHD patients in southern China, higher TC levels were associated with higher risk of mortality, while higher TG levels were related to lower risk of mortality. Patients with lower TC and higher TG levels had the best survival prognosis.